Experimental collaborations : ethnography through fieldwork devices - Estalella, Adolfo; Criado, Tomas Sanchez (EASA series., 2018)
Anthropology has historically consolidated its ethnographic mode of knowledge production around participant observation: a social and epistemic situation of fieldwork involvement maintaining a certain detachment and distance. Grounded in a series of diverse ethnographic projects in Africa, America and Europe, experimental collaboration expands our ethnographic repertoire of fieldwork devices beyond participant observation: fieldwork is carried out in collaboration with our counterparts in the field, creating an ethnographic mode whose epistemic practice is experimental and whose social engagement in the field is collaborative.